Changes of tree species diversity in peatland impacted by moderate fire severity at Teluk Meranti, Pelalawan, Riau Province, Indonesia - Lailan Syaufina; Annas Abi Hamzah (Society for Indonesian Biodiversity, 2021)
Abstract. Syaufina L, Hamzah AA. 2021. Changes of tree species diversity in peatland impacted by moderate fire severity at Teluk Meranti, Pelalawan, Riau Province, Indonesia. Biodiversitas 22: 2899-2908. Riau is one of the fire-prone provinces in Indonesia, which contributes to environmental problems not only in the country but also in neighboring countries. Peatland fire occurs annually in the province that causes transboundary haze pollution. Despite being an important threat to biodiversity, study on peatland fire impacts seems limited. The aims of this study are to analyze changes in tree species diversity due to fire and to assess fire severity. The study was conducted at Teluk Meranti Sub-district, Pelalawan District, Riau Province, Indonesia by establishing 18 sample plots in six transect lines for both burned and unburned areas. Fire severity classification was assessed by aggregate scoring of vegetation condition (individual tree damages, burned vegetation severity, and biodiversity) and soil condition (physical properties, chemical properties, and burned peat depth) indicators. The research revealed a significant change in tree species diversity from 24 species (unburned area) to 2 species (burned area) from high diversity index (2.86) to low diversity index (0.57); only 29% of burned trees can survive; average burned peat depth was about 33 cm; a significant difference of soil condition for both areas was observed. The severity of forest fires in Teluk Meranti, Pelalawan, Riau was classified as the moderate category, with a total score of 58.80%.